2002
DOI: 10.1002/path.1067
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt pathway, epithelial–stromal interactions, and malignant progression in phyllodes tumours

Abstract: In a previous study of phyllodes tumours, it has been shown that both the stroma and the epithelium can exhibit distinct molecular changes, suggesting that both are part of the neoplastic process. In view of this finding, it was decided to study stromal-epithelial interactions in these tumours by examining the Wnt-APC-beta-catenin pathway. Beta-catenin and cyclin D1 immunohistochemistry was performed on 119 phyllodes tumours. Eighty-six (72%) showed stromal nuclear beta-catenin localization and in 57% the stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
81
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 28 publications
10
81
0
2
Order By: Relevance
“…20 The Wnt pathway (bcatenin overexpression) and the IGF pathway could play a role in the development of these neoplasms. 21,22 Increased expression of KIT has been described in phyllodes tumors, [23][24][25] but KIT and PDGFRA activating mutations have not been identified so far. 23,24 Epidermal growth factor receptor (EGFR) overexpression and amplifications are common in phyllodes tumors.…”
mentioning
confidence: 99%
“…20 The Wnt pathway (bcatenin overexpression) and the IGF pathway could play a role in the development of these neoplasms. 21,22 Increased expression of KIT has been described in phyllodes tumors, [23][24][25] but KIT and PDGFRA activating mutations have not been identified so far. 23,24 Epidermal growth factor receptor (EGFR) overexpression and amplifications are common in phyllodes tumors.…”
mentioning
confidence: 99%
“…8,9 Several studies have investigated b-catenin expression in spindle cell lesions of the breast, including fibromatoses, phyllodes tumours and metaplastic carcinomas. 7,[10][11][12][13] Aberrant b-catenin expression, that is, cytoplasmic and/or nuclear, is typically found in fibromatosis, 11 however, it has also been described in metaplastic breast carcinomas 10 and phyllodes tumours. [12][13][14][15] Aberrant b-catenin expression, and particularly the nuclear localization, which can be detected by immunohistochemistry, constitutes a good surrogate marker of Wnt canonical pathway activation.…”
mentioning
confidence: 99%
“…7,[10][11][12][13] Aberrant b-catenin expression, that is, cytoplasmic and/or nuclear, is typically found in fibromatosis, 11 however, it has also been described in metaplastic breast carcinomas 10 and phyllodes tumours. [12][13][14][15] Aberrant b-catenin expression, and particularly the nuclear localization, which can be detected by immunohistochemistry, constitutes a good surrogate marker of Wnt canonical pathway activation. 1,3,10 Therefore, and on the basis of its pattern of expression and cellular localization, b-catenin has been proposed as a useful immunohistochemical marker for the differential diagnosis of spindle cell lesions; [16][17][18] however, its use has not been addressed specifically in breast tumours.…”
mentioning
confidence: 99%
“…Both the stroma and the epithelium in phyllodes tumor can show distinct molecular changes, suggesting that both are part of the neoplastic process (29). It has also been observed that there is an interdependence of growth between the stromal and the epithelial components that explains the complex morphology seen in these tumors (30,31). Stromal mitotic activity occurs in close proximity to the epithelial component, strengthening the role of stromal-epithelial interactions in progression of phyllodes tumor (30).…”
Section: Discussionmentioning
confidence: 97%